Optic nerve decompression - role in preventing traumatic ischaemic optic neuropathy: case report - Munjal, Manish; Kaur, Japneet; Rishi, Porshia; Tuli, Nitika; Bharadwaj, Iti; Munjal, Shubham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Traumatic optic neuropathy is a complication that arises due to head injury, high velocity road traffic accidents causing maxillofacial trauma. Due to involvement of optic nerve which endangers vision, there is a race against to save the vision. Endoscopic optic nerve decompression is a useful procedure for optic nerve decompression. We report a case of ischaemic optic neuropathy following road traffic accident, who underwent endoscopic optic nerve decompression within 6 hours of injury.